Discovery of a candidate binary supermassive black hole in a periodic quasar from circumbinary accretion variability. Issue 3 (10th October 2020) - Liao, Wei-Ting; Chen, Yu-Ching; Liu, Xin; Holgado, A Miguel; Guo, Hengxiao; Gruendl, Robert; Morganson, Eric; Shen, Yue; Davis, Tamara; Kessler, Richard; Martini, Paul; McMahon, Richard G; et al.
ABSTRACT: Binary supermassive black holes (BSBHs) are expected to be a generic byproduct from hierarchical galaxy formation. The final coalescence of BSBHs is thought to be the loudest gravitational wave (GW) siren, yet no confirmed BSBH is known in the GW-dominated regime. While periodic quasars have been proposed as BSBH candidates, the physical origin of the periodicity has been largely uncertain. Here, we report discovery of a periodicity ( p  = 1607 ± 7 d) at 99.95 per cent significance (with a global p value of ∼10 −3 accounting for the look elsewhere effect) in the optical light curves of a redshift 1.53 quasar, SDSS J025214.67−002813.7. Combining archival Sloan Digital Sky Survey data with new, sensitive imaging from the Dark Energy Survey, the total ∼20-yr time baseline spans ∼4.6 cycles of the observed 4.4-yr (rest frame 1.7-yr) periodicity. The light curves are best fit by a bursty model predicted by hydrodynamic simulations of circumbinary accretion discs. The periodicity is likely caused by accretion rate modulation by a milli-parsec BSBH emitting GWs, dynamically coupled to the circumbinary accretion disc. A bursty hydrodynamic variability model is statistically preferred over a smooth, sinusoidal model expected from relativistic Doppler boost, a kinematic effect proposed for PG1302−102. Furthermore, the frequency dependence of the variability amplitudes disfavours Doppler boost, lending independent support to the circumbinary accretion variability hypothesis. Given our detection rate of one BSBH candidate from circumbinary accretion variability out of 625 quasars, it suggests that future large, sensitive synoptic surveys such as the Vera C. Rubin Observatory Legacy Survey of Space and Time may be able to detect hundreds to thousands of candidate BSBHs from circumbinary accretion with direct implications for Laser Interferometer Space Antenna.